Analisis Pengaruh Multidimensi Brand Image Terhadap Minat Beli Laptop Asus ROG: Studi pada Generasi Z - Kusuma, Candra; Rahardo Suprapto, Madya; Agus Setyawan, Anton (Universitas Muhammadiyah Surakarta, 2023)
Generation Z is very interested in using laptops, such as playing games, editing videos, etc. Asus ROG is produced to fulfill these needs, but the high specifications make the price relatively more expensive than regular laptops. This study aims to analyze the effect of corporate image, product image, and owner image on Asus ROG laptop buying intention. The method used is quantitative, using SPSS software. The sampling technique uses a purposive sampling method with several criteria, one of which is the focus on seeing the response from Generation Z in Surakarta City. One hundred fifty respondents who passed the selection were obtained and can be analyzed. The results of this study are that company image and product image do not significantly affect purchase intention. In contrast, the owner's image significantly affects purchase intention. Marketers and manufacturers benefit from this research that the buying behavior of Generation Z is more caused by lifestyle.